Deposition of manure nutrients in a novel mycoalgae biofilm for Nutrient management. (April 2018) - Rajendran, Aravindan; Fox, Tyler; Reis, Cristiano Rodrigues; Wilson, Bruce; Hu, Bo
Abstract: With the increase in intensive crop and livestock production, excess application of P as fertilizer and manure contributes to the build-up of soil P levels causing eutrophication. A novel biofilm-based technology was developed to recover and reposition the nutrients in manure, producing biofilm fertilizer and the treated water with better nutrient composition. Anaerobically digested and pretreated manure was used as a medium to grow the surface-attached composite biofilm, which constitutes the selected polyphosphate accumulating fungi and nitrogen accumulating fresh water microalgae for efficient recovery of nutrients on a matrix for better biomass harvesting. Under the tested conditions in lab-scale with the pretreated digested manure, the removal efficiency of the nutrients by attached mycoalgae biofilm was 76.74% P and 76.40% N with COD removal of 65.75%. To increase the nutrient content of the biomass and for enhancing the cell growth the wastewater generated in corn ethanol process (thin stillage) was added as an external nutrient at different ratios in the digested manure. The cell growth, nutrient removal efficiency, lipid content of the biomass, COD removal and reducing sugar content at different medium conditions were evaluated. The nutrient-rich solid biofilm can be harvested by scraping off the biofilm from the matrix and the nutrient lean liquid can be discharged or further used for agriculture. The microbial biofilm assimilates the organic and inorganic components in manure and converts them into cellular constituents together with N-P-K resulting in deposition of manure nutrients in biofilm, which can be directly used as a bio-fertilizer. Graphical abstract: Highlights: Algae and Fungi can form a symbiotic attached biofilm Algae attachment on the fungi surface addresses the algae harvesting bottleneck in algae based processes The nutrients was repositioned from manure water to biofilm for manure nutrient management The solids in the medium was attached to the matrix along with the biofilm enabling better quality wastewater Additional nutrients enhanced the biofilm thickness